Argentina and the first world war - Gravil, Roger (Revista de História, 1976)
The hypothesis of Andre Gunder Frank that Latin America’s underdevelopment is partly attributable to unequal exchange in economic relations with the advanced world includes the obverse proposition that Latin America’s growth has been most substantial in periods such as wartime when links with the metropolitan countries were weakened. The most explicit statement of this view occurs in the book, Latin Ameríca: Undcrdevelopment or Revolution.